Odpowiedzi

Najlepsza Odpowiedź!
2010-01-21T19:30:48+01:00
(4x +7)² = (4x)² + 2*4x*7 + 7² = 16x² +56x + 49
(4x + y)² = 16x² + 8xy + y²
(-6a + jedna druga)² = 36a² - 6a + ¼
(⅖ x + (-2))² = 4/25x² - 8/5 x +4
(0,3x +1)² = 0,09x² +0,6x + 1
(x + y²)² = x² +2xy² + y⁴
2010-01-21T19:31:25+01:00
(4x +7)² = 16x² +56x +49

(4x + y)² = 16x²+8xy+y²

(-6a + jedna druga)² = (½ - 6a)² = ¼ - 6a + 36a²

(dwie piąte x + (-2))² = (⅖x -2)² = (4/25)x² - (4/5)x + 4

(0,3x +1)² = 0,09x²+0,6x+1

(x + y²)² = x² + 2xy² + y⁴